Production of transforming growth factor-alpha in human tumour cell lines. - Imanishi, K. (Nature Publishing Group, 1989)
Forty-one human tumour cell lines were examined for the production of epidermal growth factor (EGF)/transforming growth factor (TGF)-alpha-like activity (EGF/TGF-alpha-LA), immunoreactive (IR-) EGF and IR-TGF-alpha. EGF/TGF-alpha-LA was determined by radioreceptor assay, in which the factors with capacity to bind to EGF receptor could be detected. IR-EGF and IR-TGF-alpha were determined by the respective radioimmunoassays. Both EGF/TGF-alpha-LA and IR-TGF-alpha were detected in 11 tumour cell lines. The levels of EGF/TGF-alpha-LA correlated well with those of IR-TGF-alpha. A small amount of IR-TGF-alpha was detected in five other lines. In contrast, IR-EGF was not detectable in any of the 41. Consequently, it can be concluded that EGF/TGF-alpha-LA produced by human tumour cells is mainly TGF-alpha rather than EGF. It was also revealed that melanoma cell lines produce a large amount of TGF-alpha frequently. Gel filtration studies revealed that TGF-alpha produced by melanoma cell lines was identical to human (h) TGF-alpha(1-50), except for one line, in which IR-TGF-alpha with a different molecular size was detected. Northern blot analysis revealed that bands corresponding to hTGF-alpha mRNA were present in melanoma cell lines producing a large amount of IR-TGF-alpha, indicating that the TGF-alpha produced is the product of hTGF-alpha gene. Further studies are required to discover the actual biological roles of TGF-alpha produced by melanoma cells as well as other types of cancer cells. IMAGES: